Efficacy of Oral Prednisolone in the Management of Idiopathic Granulomatous Mastitis - Tazdina Hoque Khan; Shahidul Huq; S M Minhajul Hasan Chowdhury; Tahira Benzir; Abdullah Al Maruf; Faisal Mostafa; Syed Aminul Haque (Mediscope, 2024)
Background: Idiopathic granulomatous mastitis (IGM) is a benign inflammatory lesion of the mammary gland. Globally it possesses a major diagnostic and therapeutic problem. To date, there is no universally agreed treatment for this condition. Many treatment modalities have been attempted from conservative therapy to mastectomy but none of them has shown satisfactory results. Recent studies have shown promising results of corticosteroids on idiopathic granulomatous mastitis, so steroid therapy can be an effective treatment for idiopathic granulomatous mastitis. The goal of the study is to provide a therapeutic strategy in the future for idiopathic granulomatous mastitis. Methods: Our study included all patients with idiopathic granulomatous mastitis confirmed histologically by core needle/incisional biopsy at the general surgery unit of Chittagong Medical College Hospital and the private hospitals in the Chittagong Metropolitan City for a period of one year from October 2016 to September 2017. A total of seventy patients were included in the study provided they fulfilled predetermined criteria. All of them were included in this study by purposive sampling. After diagnosis oral prednisolone (1mg/kg/day) was given and the cases were observed by personal interview and through telephone interview. The patients were on follow-up for 06 months. Age, size of the breast lump, breast pain, nipple discharge, and skin changes were recorded in all cases. Results were analyzed using mean, percentage, and proportion as appropriate. Results: The mean age was 26.35±13.5 years ranging from 19 to 40 years. Out of 70 patients, Core cut biopsy was done in 55 patients (78.58%), and incisional biopsy with abscess drainage was performed in 15 patients (21.42%). 59 patients (84.28%) had complete recovery after a single cycle of steroid treatment, remaining 11 patients (15.72%) had recurrence, among them 6 patients were cured after 2nd cycle of steroids but unfortunately, 5 patients did not respond. Though complications were found in 50 patients, all of them made good progress in the short term. Conclusion: We recommend steroid therapy as the first-line treatment in our study. However, prospective, randomized clinical trials are needed to determine the treatment algorithm. Mediscope 2024;11(1): 22-26